Genital Cutting as Gender Oppression: Time to Revisit the WHO Paradigm - Earp, Brian D. (Frontiers in Human Dynamics, 2022)
The World Health Organization (WHO) condemns all medically unnecessary female genital cutting (FGC) that is primarily associated with people of color and the Global South, claiming that such FGC violates the human right to bodily integrity regardless of harm-level, degree of medicalization, or consent. However, it does not condemn medically unnecessary FGC that is primarily associated with Western culture, such as elective labiaplasty or genital piercing, even when performed by non-medical practitioners (e.g., body artists) or on adolescent girls. Nor does it campaign against any form of medically unnecessary intersex genital cutting (IGC) or male genital cutting (MGC), including forms that are non-consensual or comparably harmful to some types of FGC. These and other inconsistencies risk undermining the perceived authority of the WHO to pronounce on human rights. This paper considers whether the WHO can defend its selective condemnation of non-Western-associated FGC by appealing to the distinctive role of such practices in upholding patriarchal gender systems and furthering sex-based discrimination against women and girls. The paper argues that such a defense cannot succeed. To the contrary, dismantling patriarchal power structures and reducing sex-based discrimination in FGC-practicing societies requires consistent opposition to medically unnecessary, non-consensual genital cutting of all vulnerable persons, including insufficiently autonomous children, irrespective of their sex traits or socially assigned gender. This conclusion is based, in part, on an assessment of the overlapping, often mutually reinforcing, roles of different types of child genital cutting—FGC, MGC, and IGC—in reproducing oppressive gender systems. These systems, in turn, tend to subordinate women and girls as well as non-dominant males and sexual and gender minorities. The selective efforts of the WHO to eliminate only non-Western-associated FGC exposes the organization to credible accusations of racism and cultural imperialism and paradoxically undermines its own stated goals: namely, securing the long-term interests and equal rights of women and girls in FGC-practicing societies.